Beyond News Consumption: Television’s Role on Younger Audiences in Portugal - Müller, Mariana Scalabrin (Media & Jornalismo, 2024)
This study explores the relationship between television and young audiences (aged 15-24) in Portugal, in a context of rising digital media. Through the analysis of data from an online survey of 1362 participants and 42 semi-structured interviews, youths are categorized into seven profiles based on their television consumption habits and critical perspectives. A nuanced media landscape is revealed, in which television's relevance is maintained in transformed roles—from a traditional source of news to a platform for streaming content. The engagement of young viewers with television is shown to be shaped by family dynamics, educational backgrounds, and an increasing preference for digital platforms, indicating a shift towards more personalized and interactive media consumption.